Role of consciousness formation methods and their application in class work with students of specialized higher educational institutions - Olga V. Igumnova (Вестник Самарского государственного технического университета. Серия: Психолого-педагогические науки)
This article suggests the content analysis of The Federal State Educational Standards (bachelor’s and specialist’s degrees) that should be implemented in the learning process of specialized higher educational institutions that report to the Federal Penitentiary Service of Russia. The FSES content analysis allows specifying the priority educational directions realized in class work with students. These directions of educational work must be focused on the students’ mindset formation by the means of the methods of the prospective penal officers’ consciousness formation such as convincing method, ethic discussion, clarification, debate, explanation, case study, example-oriented method. The use of some educational techniques within mentioned above methods is given reasons for.